Inquiry a districtwide approach to staff and student learning - Dana, Nancy Fichtman 1964-
Now that federal and state initiatives require school districts to provide job-embedded professional development, the next step is making it happen. This book helps districts define, develop, and implement a systematic inquiry-based process with a laser-like focus on both adult and student learning